A differential evolution-based algorithm for calculating beamformers in MIMO systems - Jimenez, Samantha P.; Maciel, Fermin M.; Soriano-Equigua, Leonel; Castillo, Victor H.; Alvarez, Jose Luis (Iberian Conference on Information Systems and Technologies (Print), 2015)
Calculating the beamformers and combiners in multiple-input multiple-output (MIMO) wireless telecommunication systems is an important research issue. This calculation is significant because helps to analyze the overall system performance. Several authors proposed different algorithms for this process. However, these algorithms require a great number of iterations for converging. Considering reduction in the algorithm convergence time, evolutionary computing strategies focus on the optimization of processes. An approach of evolutionary computing is the differential evolution. In order to improve performance in MIMO telecommunication systems, this work proposes a differential evolution-based algorithm for calculating beamformers. The experiment results show that, under the studied scenario, the proposed algorithm improves the convergence time and the overall system performance.